New Scale Insects (Homoptera: Coccoidea) in the Greek Entomofauna - Kozar, F.; Paloukis, S.; Papadopoulos, N. (ENTOMOLOGIA HELLENICA, 1991)
Collection of scale insects in Greece in 1990 – 1991 provided 71 species. Among them, 31 species were new for the Greek fauna. The total number of known species is 143 in Greece. Host plant’s levels of infestation and phonological data are also presented. The results show that scale insect fauna of this country needs further intensive studies.